Knowledge levels of general dental practitioners and senior dental students about antibiotic prophylactic measures in children with heart disease in Isfahan in 2010 - Neda Ahmadi Rozbahani; Seyed Ebrahim Jabarifar; Romina Mazaheri; Habibolah Rezvan (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Infectious endocarditis might occur by oral microbial flora subsequent to dental procedures leading to bleeding in the oral cavity. Therefore, the dental practitioner should be able to prescribe appropriate antibiotics in the prophylactic measures against bacterial endocarditis during dental procedures. The aim of this study was to evaluate the knowledge of general dental practitioners and senior dental students about the principles of antibiotic prophylaxis in children with cardiac problems in Isfahan.Materials and methods: This cross-sectional study was carried out in winter 2010 in Isfahan. After data collection, a questionnaire was designed and distributed among 111 male and female general dental practitioners and senior dental students. Data was analyzed by one-way ANOVA, Levene's test and t-test using SPSS 11 (α = 0.05).Results: The results showed that senior dental students (mean=12.28 ± 3.12, p value = 0.018) and recently graduated dental practitioners (mean 12.21 ± 3.33, p value = 0.031) were in the medium acceptable level of knowledge compared to other groups with more job experiences. General dental practitioners with more than 17 years of job experience (mean = 8.84 ± 2.66, p value = 0.06) achieved the lowest score.Conclusion: Recently graduated dental practitioners and senior dental students had a higher knowledge level about the principles of antibiotic prophylaxis in children suffering from heart diseases, which might be attributed to being in the academic atmosphere of the university and their greater and easier access to the relevant references. Key words: Antibiotic prophylaxis, Endocarditis, General dental practitioner.